The Serum Expression of Selected miRNAs in Pulmonary Sarcoidosis with/without Löfgren’s Syndrome - Eva Novosadova; Alzbeta Chabronova; Vitezslav Kolek; Martin Petrek; Zdenka Navratilova (Mediators of Inflammation)
Purpose. Pulmonary sarcoidosis is associated with dysregulated expression of intracellular miRNAs. There is however only little information on extracellular miRNAs and their association with the disease course in sarcoidosis. We therefore assessed serum miRNAs in sarcoidosis classified according to the presence of Löfgren’s syndrome (LS) as a hallmark of good prognosis in contrast to more advanced disease course. Methods. RT-PCR was used to assess 35 miRNAs in 13 healthy controls and 24 sarcoidosis patients (12 with X-ray (CXR) stage ≤ 1 and LS and 12 with insidious onset and CXR stage ≥ 3). Results. Compared to controls, we consistently observed dysregulated expressions of miR-146, miR-16, miR-425-5p, and miR-93-5p in both sarcoidosis groups irrespective of disease course. Specifically, patients without LS had dysregulated expressions of miR-150-5p, miR-1, and miR-212 compared to controls. Patients with LS had dysregulated expressions of miR-21-5p and miR-340-5p compared to controls. Bioinformatics predicted consistently “Pathways in cancer” to be modulated by both altered profiles in patients with/without LS. Three miRNAs (miR-21-5p, miR-340-5p, and miR-212-3p) differed between our patients with LS and those without LS; their cumulative effect may modulate “TGF-β signalling pathway.” Conclusions. Further study should focus on possible applications of serum miRNAs for diagnostics follow-up and for prognosis.